Development and Validation of Measure on Student-Teacher Relationship in the Indian Context - Yadav, Shreshtha; Kohli, Neena; Yadav, Anil Kumar; Naveen,; Tiwari, Trayambak; Mishra, Tarun (Frontiers in Education, 2022)
The notion that the student-teacher relationship is quintessential for the holistic development and success of students has been well established through various researches. A considerable number of studies have been conducted in western countries and various scales have been developed to measure student -teacher relationship. These scales have been extended to various cultural contexts. However, very few studies have been found to focus on the suitability and applicability of these scales and theories of student-teacher relationship in the Indian context. In the western context, most of the studies on the student-teacher relationship were based on the attachment theory. Whereas, in the context of Indian culture, student-teacher relationship functions beyond the boundaries of attachment theory. It is well acknowledged that Indian culture differs vastly from other cultures. Given the uniqueness of Indian culture present study advocated that nature of student-teacher relationship in the Indian context is significantly different from western countries. There was a need to develop a scale for measuring student-teacher relationship in the Indian context. This study intended to construct a scale on student-teacher relationship in the Indian context. Standard procedure was followed in the process of scale construction. Results of study one illustrated a four factor (dedication, trust, respect, obedience) model of student-teacher relationship and second study confirmed this model and ensured reliability and validity of the scale.